Essays on Islam and Indian history - Eaton, Richard M (New Delhi Oxford University Press, 2000)
The essays in this volume fall into three categories-historiography and Indo-Islamic civilization. The first three essays explores the place of Islam in world history, religious conversion as a world historical theme, and Calicut in world history. The fou
Keywords: India-History-Essays; Islam-India-History